Transformasi Fungsi dan Bentuk Bangunan - Reaktivasi Stasiun Kereta Api Garut dan Pasirjengkol - Tasya Fatihah; Ilma Nurfadlilawati; Fakhrisa Nur Paramarta; Wiwik Dwi Pratiwi (Universitas Udayana, 2024)
The reactivation of several train stations is part of PT. Kereta Api Indonesia's attempts to enhance railway services. In doing so, it initiated the reactivation of the Garut-Cibatu railway, which ceased operations in 1983. The 2018 National Railway Master Plan (RIPNAS) and Garut City Regional Spatial Plan (RTRWK) support the reactivation of this railway line to stimulate economic growth and improve tourism accessibility. This reactivation involves planning for the whole railway zone, including enhancing the overall physical quality of the Garut-Cibatu line and reopening several railway stations. This research focuses on the transformation of Garut Station, located in the Garut Kota District, and Pasirjengkol Station, located in the Sukawening District. As a result, both stations have experienced changes, notably the addition of new buildings. This implies transformations in building functions, station layouts, and architectural styles. This study aims to comprehend the changes and their impact on functions that support the operation of the railway and passenger experiences. It employs a qualitative method with descriptive analysis by combining secondary data from historical literature studies and primary data from documentation and interviews with relevant respondents.Keywords: railway station; transformation; function and form; operational function; passenger experience AbstrakReaktivasi beberapa stasiun kereta api merupakan bagian dari upaya PT. Kereta Api Indonesia untuk meningkatkan pelayanan perkeretaapian. Di dalam pelaksanaannya, diinisiasi untuk mereaktivasi jalur kereta api Garut-Cibatu yang berhenti beroperasi pada tahun 1983. Rencana Induk Perkeretaapian Nasional (RIPNAS) tahun 2018 dan Rencana Tata Ruang Wilayah Kota (RTRWK) Garut mendukung reaktivasi jalur kereta api ini sebagai sarana untuk mendorong pertumbuhan ekonomi dan memudahkan akses pariwisata. Reaktivasi ini melibatkan penataan kawasan yang mencakup peningkatan kualitas fisik serta beroperasinya kembali beberapa stasiun kereta api. Stasiun Garut yang berlokasi di Kecamatan Garut Kota dan Stasiun Pasirjengkol di Kecamatan Sukawening menjadi fokus penelitian ini karena adanya transformasi stasiun kereta api yang terjadi pada kedua stasiun berupa penambahan massa bangunan. Transformasi ini mencakup perubahan bentuk fungsi bangunan, tata letak stasiun, dan gaya arsitektur. Penelitian ini bertujuan untuk memahami perubahan yang terjadi dan dampaknya terhadap fungsi-fungsi pendukung operasional, dan pengalaman pengguna stasiun. Penelitian ini menggunakan metode kualitatif dengan analisis deskriptif dengan menggabungkan data sekunder dari studi literatur Sejarah, dengan data primer dari dokumentasi serta wawancara dengan pihak yang relevan.Kata kunci: stasiun kereta api; transformasi; fungsi dan bentuk; fungsi operasional; pengalaman pengguna